Analisis Pemberian Insentif Dalam Meningkatkan Motivasi Dan Kinerja Karyawan Studi Kasus Perusahaan Tour Travel PT. Menara Dunia Tour Travel Di Surabaya - Meiyola Krisma Agatha; Rizki Luthfi Aulia; Hwihanus Hwihanus (Jurnal Mutiara Ilmu Akuntansi, 2024)
The purpose of this research is to find out: (1) Providing incentives in an effort to improve employee performance at the travel tour company PT. Menara Dunia Tour Travel which has been running, (2) How incentives should be given in an effort to improve the performance of PT. Menara Dunia Tour Travel. This research method uses a qualitative descriptive approach. Data collection techniques include direct interviews with company leaders and employees, observation and documentation. The research results show (1) The incentive system provided by the company to its employees is in the form of material and non-material incentives in the form of bonuses, social security, awards, work training and joint holidays. Meanwhile, the things that drive employee performance and motivation are employee quality, employee quantity, and employee attendance or discipline. The results of this research are that providing incentives can increase work enthusiasm in increasing achievement, increase loyalty, discipline and responsibility for the position, and most importantly can improve employee performance, (2) By looking at the results of the analysis which shows that the program The incentives implemented by PT. Menara Dunia Tour Travel For this reason, companies are expected to be able to maintain and improve their policy of providing incentives in an effort to improve employee performance.